2014
DOI: 10.1111/jgh.12554
|View full text |Cite|
|
Sign up to set email alerts
|

Role of lamivudine with transarterial chemoembolization in the survival of patients with hepatocellular carcinoma

Abstract: Lamivudine therapy could reduce HBV activation and improve survival of HCC patients treated with TACE. Lamivudine therapy and AFP level are two independent factors affecting OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 29 publications
(56 reference statements)
0
25
0
Order By: Relevance
“…Xu et al reported that the level of HBV-DNA became undetectable in 45.6% of the patients treated with lamivudine in combination with TACE, while only 11.2% of the patients treated with TACE alone had a undetectable HBV-DNA, and antiviral treatment enhanced the one-, two-, and three-year survival rates from 60%, 48%, and 48% to 83%, 69%, and 58%, respectively [47]. In a randomized control study, Jang et al found that patients who received lamivudine in preemptive therapy from the start of transarterial chemo-lipiodolization have a much lower chance of viral reactivation [48].…”
Section: Antiviral Treatment In Transcatheter Arterial Chemoembolizationmentioning
confidence: 96%
“…Xu et al reported that the level of HBV-DNA became undetectable in 45.6% of the patients treated with lamivudine in combination with TACE, while only 11.2% of the patients treated with TACE alone had a undetectable HBV-DNA, and antiviral treatment enhanced the one-, two-, and three-year survival rates from 60%, 48%, and 48% to 83%, 69%, and 58%, respectively [47]. In a randomized control study, Jang et al found that patients who received lamivudine in preemptive therapy from the start of transarterial chemo-lipiodolization have a much lower chance of viral reactivation [48].…”
Section: Antiviral Treatment In Transcatheter Arterial Chemoembolizationmentioning
confidence: 96%
“…The characteristics and quality of the studies are summarized in Table 1. Nucleotide analogs lamivudine alone was used in the study from Yoshida et al and Xu et al [16, 17]. In other studies, lamivudine, adefovir, telbivudine, and entecavir were used.…”
Section: Resultsmentioning
confidence: 99%
“…These include HBeAg status, viral load, baseline liver function, age, gender, and the intensity of LRT and the use of anthracyclines [80] . However, the data for HBV reactivation following TACE remains somewhat inconclusive, with some studies suggesting increase risk, whereas other studies have demonstrated no changes, or even decline in HBV DNA after chemoembolization [81,82] . The mechanism underlying the decline in viral load remains unclear, and may be due to the natural fluctuation that is independent of the TACE, or possibly from a reduction in tumor load, which may support HBV replication or impair the host immunity.…”
Section: Antiviral Therapy For Hcc Patients Undergoing Locoregional Tmentioning
confidence: 94%